Satisfaction with the activities of reeves, mayors and presidents of cities and evaluation of the level of representation of the interests by local goverments - Alberski, Robert (Political Preferences, 2013)
This part of the report describes two problems: evaluation of the activi- ties of reeves, mayors and presidents of cities and the problem of representing the interests of the residents by local governments. In a survey conducted in late 2012, we decided to verify two hypotheses. By the first, trust in local government results from the positive evaluation of reeves, mayors and presidents of cities activities. Second hypothesis assumes that trust is founded by the belief of the local community members, that the local governments represent their interests. The results indicate that the majority of the respondents are restra- inedly satisfied with the activities of their reeves, mayors and presidents of cities. However, the majority of respondents said that local governments do not represent their interests.